1997
DOI: 10.1128/jb.179.24.7776-7783.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a gene from Streptomyces scabies encoding a putative pathogenicity factor

Abstract: We cloned a 9.4-kb DNA fragment from Streptomyces scabies ATCC 41973 that allows the nonpathogen Streptomyces lividans 66 TK24 to necrotize and colonize potato tuber slices and produce scab-like symptoms on potato minitubers. Deletion analysis demonstrated that activity was conferred by a 1.6-kb DNA region. Sequence analysis of a 2.4-kb DNA fragment spanning the DNA region necessary for activity revealed three open reading frames (ORFs). The deduced amino acid sequence of ORF1, designated ORFtnp, showed high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 35 publications
1
46
1
1
Order By: Relevance
“…among the actinobacterial endoflora of wheat that was observed in the present study was also noted by Sardi et al (35) on field crops and Italian native plants and as a result of the molecular characterization of the bacterial population within potatoes (36). However, these results would suggest that the endophytic microflora of wheat is different from that reported in maize, where the genus Microbispora, followed by Streptomyces and Streptosporangium, was most commonly isolated (9). However, the differences between the observed endophytic actinobacterial communities between these plants are the relative proportions of one genus to another, possibly due to bias in the isolation method, since all of the genera isolated from maize plant tissue were also isolated from wheat.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…among the actinobacterial endoflora of wheat that was observed in the present study was also noted by Sardi et al (35) on field crops and Italian native plants and as a result of the molecular characterization of the bacterial population within potatoes (36). However, these results would suggest that the endophytic microflora of wheat is different from that reported in maize, where the genus Microbispora, followed by Streptomyces and Streptosporangium, was most commonly isolated (9). However, the differences between the observed endophytic actinobacterial communities between these plants are the relative proportions of one genus to another, possibly due to bias in the isolation method, since all of the genera isolated from maize plant tissue were also isolated from wheat.…”
Section: Discussioncontrasting
confidence: 56%
“…These included S. scabies ATCC 49173, S. acidiscabies ATCC 49003, S. setonii ATCC 25497, and S. caviscabies ATCC 51928. The nec1 gene fragment was amplified with the Nf (5Ј-AT GAGCGCGAACGGAAGCCCCGGA) and Nr (5Ј-GCAGGTCGTCACGAAG GATCG) primers (9). These primers were used in the following 25-l reaction mixture: primers (200 ng l Ϫ1 ), 1 l each; 5ϫ Taq buffer (including deoxynucleoside triphosphates), 5 l; water, 15.5 l; Taq polymerase (2 U l Ϫ1 ), 0.5 l; and template DNA, 2 l. The following thermal profile was used: 95°C for 2 min; followed by 30 cycles of 95°C for 1 min, 60°C for 1 min, and 72°C for 2 min; and then a 15°C soak.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis of the region also identified truncated homologs of other genes, including a pathogenicity-associated transposase. The chimeric architecture of the txt region in particular serves to further support our model of the recent pathogenicity island-mediated emergence of taxonomically diverse Streptomyces pathogens (4,5,13). Our analysis of the 5-kb region did not reveal the presence of any ORFs resembling the class I P450 redox partner proteins, ferredoxin or the FAD-containing NAD(P)H ferredoxin oxidoreductase.…”
Section: Discussionmentioning
confidence: 83%
“…The biosynthesis of thaxtomin has been characterized (19,20,29), and transcription of the biosynthetic genes is activated by the AraC family regulator TxtR, which binds cellobiose to facilitate transcription (25). Scab-causing streptomycetes also contain a novel necrogenic protein, Nec1, which is important in pathogenesis and may be involved in the suppression of plant defenses (10,24). Recently, sequencing of a self-mobilizable pathogenicity island in S. turgidiscabies revealed that a putative tomatinase gene was conserved among three phylogenetically distinct scab-causing streptomycetes, S. turgidiscabies Car8, S. acidiscabies, and S. scabies (also known as S. scabiei) 87-22 (28).…”
mentioning
confidence: 99%